Evaluation on substitution of energy transition—An empirical analysis based on factor elasticity - Li, Liang; Xiong, Weiwei; Duan, Weijing; Xiong, Yiran (Frontiers in Energy Research, 2023)
The study explores into the dynamic change features and technological differences in substitution between factors and energy sources for various types of China’s technological progresses from 1990 to 2020. The measurement for such a study is conducted from the perspective of factor substitution by employing the transcendental logarithmic production function. The results reveal that the sources of contribution to China’s economic development are mainly attributed to non-energy factors such as capital and labor, as capital and labor can effectively substitute energy, and non-fossil energy sources possess certain comparative advantages over fossil energy sources in terms of technology within energy factors. With such an increase in substitution, the trend of clean energy substitution for fossil energy is irreversible. Accordingly, it is proposed that the path for energy conservation and consumption reduction via energy transformation be achieved by increasing input into capital and labor to improve the utilization efficiency of these two factors from the perspective of factor substitution. Meanwhile, preferences should be delivered for the development of non-fossil energy sources in terms of technology bias and input scale.